Exploring Content Game Elements to Support Gamification Design in Educational Systems: Narrative and Storytelling - Palomino, Paula T.; Toda, Armando M.; Oliveira, Wilk; Rodrigues, Luiz; Cristea, Alexandra I.; Isotani, Seiji (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
Several studies on gamification applied to educational systems aim at encouraging students to do certain tasks and improving their learning. According to the literature, most gamification frameworks are structural (e.g. scoring systems, ranking, etc.), with few content-related frameworks. To the best of our knowledge, there is no narrative framework available. Therefore, this paper analyses data obtained from a survey about the students' preferred game elements in an educational context, with a focus on Association Rules found concerning Narrative and Storytelling elements. We show that Narrative and Storytelling are tightly related and provide insights of their use in groups with other game elements, enabling the creation of gamified strategies based on these aspects.